2012
DOI: 10.2355/isijinternational.52.402
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Validation of an Electric Arc Furnace: Part 1, Heat and Mass Transfer

Abstract: The following paper presents an approach to the mathematical modeling of heat and mass transfer processes in a 3-phase, 80 MVA AC, electric arc furnace (EAF) and represents a continuation of our work on modeling the electric and hydraulic EAF processes. This paper represents part 1 of the complete model and addresses issues on modeling the mass, temperature and energy processes in the EAF, while part 2 of the paper focuses solely on the issues related to the thermo-chemical relations and reactions in the EAF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 16 publications
2
103
0
Order By: Relevance
“…3 to 6. It can be observed that results of the proposed algorithm are comparable to constant values of arc energy distribution reported by Logar et al 18) and Ghobara 20) at comparable input conditions. The relationship between the arc length, arc current and the calculated arc power is shown in Fig.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…3 to 6. It can be observed that results of the proposed algorithm are comparable to constant values of arc energy distribution reported by Logar et al 18) and Ghobara 20) at comparable input conditions. The relationship between the arc length, arc current and the calculated arc power is shown in Fig.…”
Section: Resultssupporting
confidence: 73%
“…The main difference between the results appears due to constant conductive heat transfer in Makarov's work, which does not change by altering the arc lengths. Hence, the proposed model indicates slightly different percentage of radiated heat when it is compared to the result reported by Makarov et al 21) The second validation of the arc module is performed by integrating the module into a comprehensive EAF model 18,19) in order to obtain the EAF bath temperatures and compare them with the measured EAF operational data. The measurements were performed on a 105 ton EAF, with 85 MVA transformer.…”
Section: Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…In times of continuously growing computational capacity, the complexity of the dynamic process simulation models has increased due to the consideration of more and more phenomena. Logar et al [2][3][4] presented a comprehensive deterministic EAF model, which is based on fundamental physical and mathematical equations. The model includes all main thermal, chemical, and mass transfer phenomena in the EAF.…”
Section: Introductionmentioning
confidence: 99%